2006
DOI: 10.1248/bpb.29.2106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astaxanthin Supplementation on Exercise-Induced Fatigue in Mice

Abstract: The present study was designed to determine the effect of astaxanthin on endurance capacity in male mice aged 4 weeks. Mice were given orally either vehicle or astaxanthin (1.2, 6, or 30 mg/kg body weight) by stomach intubation for 5 weeks. The astaxanthin group showed a significant increase in swimming time to exhaustion as compared to the control group. Blood lactate concentration in the astaxanthin groups was significantly lower than in the control group. In the control group, plasma non-esterfied fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 18 publications
(17 reference statements)
7
85
1
Order By: Relevance
“…Blood lactate is an important indicator for judging the degree of fatigue (Yu et al, 2008;Lin et al, 2005). It has been reported that blood lactate accumulates during exercise (Grenhaff and Timmonns, 1998;Ikeuchi et al, 2006). Results in Figure 1 showed that the BLA of mice in 0.3 ml safflower extract group (C) was significantly lower than that in control group (A, p < 0.05) after forced swimming exercise.…”
Section: Results and Dicussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Blood lactate is an important indicator for judging the degree of fatigue (Yu et al, 2008;Lin et al, 2005). It has been reported that blood lactate accumulates during exercise (Grenhaff and Timmonns, 1998;Ikeuchi et al, 2006). Results in Figure 1 showed that the BLA of mice in 0.3 ml safflower extract group (C) was significantly lower than that in control group (A, p < 0.05) after forced swimming exercise.…”
Section: Results and Dicussionmentioning
confidence: 84%
“…Each of the mice had a weight attached (6% body weight) to the tail for the duration of the swimming exercise. The mice were assessed to be fatigued when they failed to rise to the surface of the water to breathe within 5 s (Ikeuchi et al, 2006(Ikeuchi et al, , 2009 …”
Section: Determination Of Sport Performance In Mice Swimming Endurancmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that astaxanthin enhances lipid metabolism and endurance 20,21) , and enhanced endurance may be associated with the capillarization observed in the CA group, and the prevention of capillary regression observed in the HA group. Despite these findings, it is important to note that astaxanthin does not prevent muscle atrophy.…”
Section: Discussionmentioning
confidence: 89%
“…Second, exercise causes the production and accumulation of products of metabolism, such as lactic acid. Third, exercise promotes the mobilization and consumption of energy sources such as glycogen (Ikeuchi et al, 2006). In addition, overexercise diminishes the brain's supply of oxygen, which leads to fatigue.…”
Section: Anti-fatigue Activitymentioning
confidence: 99%